Facile synthesis and characterisation of uniform and monodispersed In(OH)3 and In2O3 microcubes. (1st September 2017) - Xu, Zhenhe; Lin, Junying; Yu, He; Sun, Yaguang; Ding, Fu; Fan, Hongtao; Shi, Shan; Fang, Qinghong; Bi, Yanfeng; Gao, Yu
Abstract : In(OH)3 microcubes have been successfully synthesised by a direct precipitation in solution at room temperature without using any surfactant or template. Furthermore, the In2 O3 microcubes were obtained through calcining the In(OH)3 microcubes. The results show that the as‐prepared In(OH)3 and In2 O3 products have a cube shape with a mean edge length of 190 and 155 nm, respectively. The self‐assembly process via orientation attachment is proposed in order to explain the growth mechanism for the microcubes. Upon ultraviolet excitation, a broad blue photoluminescence emission with its maximum intensity centred at 466 nm is shown, which is due to the oxygen deficiencies in the In2 O3 microcubes. It endows these microcubes with potential application, such as liquid crystal devices, solar‐energy conversion, optical and electric devices.